Representing Clinical Narratives Using Conceptual Graphs - Baud, R. H.; Rassinoux, A. M.; Wagner, J. C.; Lovis, C.; Juge, C.; Alpay, L. L.; Michel, P. A.; Degoulet, P.; Scherrer, J. R. (Methods of Information in Medicine, 1995)
The analysis of medical narratives and the generation of natural language expressions are strongly dependent on the existence of an adequate representation language. Such a language has to be expressive enough in order to handle the complexity of human reasoning in the domain. Sowa’s Conceptual Graphs (CG) are an answer, and this paper presents a multilingual implementation, using French, English and German. Current developments demonstrate the feasibility of an approach to natural Language Understanding where semantic aspects are dominant, in contrast, to syntax driven methods. The basic idea is to aggregate blocks of words according to semantic compatibility rules, following a method called Proximity Processing. The CG representation is gradually built, starting from single words in a semantic lexicon, to finally give a complete representation of the sentence under the form of a single CG. The process is dependent on specific rules of the medical domain, and for this reason is largely controlled by the declarative knowledge of the medical Linguistic Knowlege Base.
Keywords: Natural Language Processing; Knowledge Representation; Conceptual Graph; Medical Record